2010
DOI: 10.1016/j.devcel.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

An Early Developmental Role for miRNAs in the Maintenance of Extraembryonic Stem Cells in the Mouse Embryo

Abstract: The two first cell fate decisions taken in the mammalian embryo generate three distinct cell lineages: one embryonic, the epiblast, and two extraembryonic, the trophoblast and primitive endoderm. miRNAs are essential for early development, but it is not known if they are utilized in the same way in these three lineages. We find that in the pluripotent epiblast they inhibit apoptosis by blocking the expression of the proapoptotic protein Bcl2l11 (Bim) but play little role in the initiation of gastrulation. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 52 publications
2
104
0
Order By: Relevance
“…However, the inability to achieve full rescue by p21 silencing suggests that other yet-to-be identified CUL4B substrates likely also contribute to the cell cycle arrest that is triggered by CUL4B inactivation. Spruce et al [38] recently demonstrated that inhibition of p21 expression by miRNA was required to maintain the trophoblast stem cell compartment. Our findings suggest that p21 accumulation is a significant factor that contributes to the developmental defects of the extra-embryonic tissues and embryonic lethality of Cul4b-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inability to achieve full rescue by p21 silencing suggests that other yet-to-be identified CUL4B substrates likely also contribute to the cell cycle arrest that is triggered by CUL4B inactivation. Spruce et al [38] recently demonstrated that inhibition of p21 expression by miRNA was required to maintain the trophoblast stem cell compartment. Our findings suggest that p21 accumulation is a significant factor that contributes to the developmental defects of the extra-embryonic tissues and embryonic lethality of Cul4b-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…1). 15 In agreement with there not being any major perturbation in Nodal signaling in embryos lacking miRNAs, mesoderm formation is initiated, although with a one day delay, in the posterior epiblast and there is no expansion of neuroectoderm markers. The delay in mesoderm formation mimics that of Nodal restriction in these embryos (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 51%
“…1). 15 Additionally we found that the genes coding for the Nodal processing proteins Spc1 and Spc4 are expressed in the trophoblast, the Nodal co-activator Cripto is robustly expressed in the epiblast and Lefty1 expression is not expanded in Dicer zygotic deletion of Dgcr8 in mouse has shown that miRNAs are neither required for early pre-implantation development nor trophectoderm specification. 13 Given the major role that extra-embryonic tissues have on the development of the mammalian epiblast it is necessary to consider them when analysing the effect of miRNAs deletion on embryo development.…”
Section: 3mentioning
confidence: 94%
See 2 more Smart Citations